Macrolides and viral infections: focus on azithromycin in COVID-19 pathology - Pani, Arianna (Int J Antimicrob Agents, 2020)
The emergence of the new COVID-19 virus is proving to be a challenge in seeking effective therapies. Since the most severe clinical manifestation of COVID-19 appears to be a severe acute respiratory syndrome, azithromycin has been proposed as a potential treatment. Azithromycin is known to have immunomodulating and antiviral properties. In vitro studies have demonstrated the capacity of azithromycin in reducing production of pro-inflammatory cytokines such as IL-8, IL-6, TNF alpha, reduce oxidative stress, and modulate T-helper functions. At the same time there are multiple clinical evidences of the role of azithromycin in acute respiratory distress syndrome and against Middle East Respiratory syndrome (MERS). Some preliminary evidence has demonstrated controversial results regarding efficacy of azithromycin in combination with hydroxychloroquine in COVID-19. First, a French trial demonstrated 100% virological negativizing of six patients treated with azithromycin plus hydroxychloroquine vs. 57.1% of patients treated with only hydroxychloroquine and 12.5% of the control group (P < 0.05). On the other hand, another case series revealed no efficacy at all on 11 patients treated with the same combination and doses. Furthermore, there are some concerns regarding the association of azithromycin and hydroxychloroquine because of potential QT prolongation. In fact, both drugs have this as a potential side effect and evidence regarding the safe use of this combination is controversial. Despite the necessity to quickly find solutions for COVID-19, extreme caution must be used in evaluating the risk-benefit balance. However, based on preclinical and clinical evidence and some preliminary results in COVID-19, azithromycin could have potential in the fight against this new disease.